Academic achievement and time concept of the learner - R C Grobler; C PH Myburgh (AOSIS, 2001)
The time concept and academic achievement of a group of high school learners were investigated and the results are described in this article. Opsomming Die tydkonsep en akademiese prestasie van 'n groep hoërskool leerders is ondersoek en die resultate is beskryf in hierdie artikel. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.